Self-perceived emotional intelligence in leadership of administrative academic staff / Sueb Ibrahim - Ibrahim, Sueb (Universiti Teknologi MARA Cawangan Sarawak, 2017)
Research on effective educational leadership and emotional intelligence is growing. There still remains a gap in the relationship that exists between emotional intelligence and educational leadership especially at higher education institutions such as colleges and universities. The main aim of this study was to identify the self-perceived emotional intelligence in leadership of a university's administrative academic staff. A total of 20 (out of 26) administrative academic staff participated in this study. Two research instruments that were adapted for this study were Bass and Avolio's Multifactor Leadership Questionnaire (MLQ5X Form) and Mayer - Salovey - Caruso Emotional Intelligence Test (MSCEIT). The findings indicated that the administrative academic staff perceived themselves as exhibiting a highly transformational leadership style as compared to the other two leadership styles, namely, transactional and laissez- faire. The findings also revealed that the administrative academic staff assessed themselves as demonstrating more on managing emotions as compared to the other three emotional branches, namely perceiving emotions, facilitating emotions, and understanding emotions. It also revealed that there was a weak but significant relationship between the transactional leadership relationship and emotional intelligence while the other two leadership styles did not indicate any significant relationship